Memory of chirality in a room temperature flow electrochemical reactor - Tomas Hardwick (Nature Portfolio, 2020)
Abstract Chiral compounds have become of great interest to the pharmaceutical industry as they possess various biological activities. Concurrently, the concept of “memory of chirality” has been proven as a powerful tool in asymmetric synthesis, while flow chemistry has begun its rise as a new enabling technology to add to the ever increasing arsenal of techniques available to the modern day chemist. Here, we have employed a new simple electrochemical microreactor design to oxidise an l-proline derivative at room temperature in continuous flow. Compared to batch, organic electrosynthesis via microflow reactors are advantageous because they allow shorter reaction times, optimization and scale up, safer working environments, and high selectivities (e.g. reduce overoxidation). Flow electrochemical reactors also provide high surface-to-volume ratios and impart the possibility of excluding the supporting electrolyte due to a very short interelectrode distance. By the comparison of Hofer Moest type electrochemical oxidations at room temperature in batch and flow, we conclude that continuous flow electrolysis is superior to batch, producing a good yield (71%) and a higher enantiomeric excess (64%). These results show that continuous flow has the potential to act as a new enabling technology for asymmetric synthesis to replace some aspects of conventional batch electrochemical processes.